Improving Students Writing Ability and Creativity in Procedure Text Using Technological Pedagogic Content Knowledge (TPCK) - Ariyani, Etika (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Improving Students Writing Ability & Creativity in Procedure Text through Technology Pedagogic Content Knowledge. This study aims to determine the effectiveness of the TPCK-based learning model on Canva application to improve students' writing ability and creativity in writing text procedures. This research is classroom action research consisting of 2 cycles, each cycle consists of 4 main stages, namely planning, implementation, observation and reflection. The subjects in this study were 25 students of class X SMAN I Kediri, West Lombok, West Nusa Tenggara. Data were obtained through observation, interviews, writing assignments and field notes. The data were analyzed descriptively qualitatively including collecting data, coding, comparing, making interpretations and reporting the results. The results showed that the application of project-based learning experiences can improve students' writing skills and creativity. This project-based learning experience can significantly increase students' curiosity, interest and motivation, encourage changes in students' attitudes and behaviors to develop their writing skills and creativity, teachers can monitor and assess students' progress through the results of student work projects regularly. The results showed that the average score of students in the pre-test 11.58 increased to 15.84 in the post test with a difference of 4.26. The findings mean that the technology-based learning model can significantly improve students' writing skills and creativity in writing procedure texts.